Nursing Students’ Perceptions of Using ChatGPT in a Written Assignment - Newton, Lorelei; Wignall, Angela; Fullerton, Claire (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2025)
Introduction: The availability and use of artificial intelligence (AI) tools is accelerating significantly. As these technologies proliferate, many post-secondary institutions have responded by banning students from using AI tools such as ChatGPT and framing the conversation as breaches of academic integrity.Background: Despite these institutional responses, many students adopt these tools as part of their learning journey. In health care settings, the adoption of such tools in the context of patient care provision is a reality. Consequently, there is a relevant pedagogical opportunity to examine how such tools inform the experiential learning of nursing students and their future practice.Methods: To address the dearth of information regarding nursing students’ perceptions of using AI tools, a Canadian university teaching team incorporated ChatGPT into an undergraduate nursing course assignment. A pilot quasi-experimental pre-post-test survey design was employed to examine student perceptions of using ChatGPT. After obtaining institutional ethics approval, a neutral third party collected the anonymous data.Findings: Pilot study results highlighted significant student concerns regarding the ethics of using AI tools. Additionally, students described such tools as meaningful avenues to support learning access and equity. Finally, students identified a high probability of use of AI tools in their future practice, suggesting that exposure and support during learning can positively influence responses to these tools in practice settings.Conclusion: The students surveyed are now practising nurses; thus, findings may provide insight into perceptions of new nurses regarding the integration of AI to support competencies required by the nurses of tomorrow.